2022
DOI: 10.3390/ijerph19053064
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Adolescent Physical Activity Levels and Their Relationship with Body Image and Nutritional Habits

Abstract: The main objective of this research article was to make a cluster analysis in Compulsory Secondary Education students with regard to their physical activity levels, their relationship with nutritional habits and body perception. In this study, a total of 1089 students participated, to whom a battery of tests was given in order to assess three aspects: levels of physical activity, food consumption habits and perception of body image. The main results indicated that the adolescent sample presented high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…According to the first specific objective, to establish the differences between male and female adolescents in anthropometric and derived variables, psychological state, and physical fitness, the results of the present study are similar to those found in previous studies. Adolescent males showed a higher level of physical activity than females, in line with previous research [ 7 , 17 ]. With respect to physical fitness, males obtained higher scores in all the variables analyzed, except for the sit-and-reach test, corroborating the results of previous research [ 10 , 73 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the first specific objective, to establish the differences between male and female adolescents in anthropometric and derived variables, psychological state, and physical fitness, the results of the present study are similar to those found in previous studies. Adolescent males showed a higher level of physical activity than females, in line with previous research [ 7 , 17 ]. With respect to physical fitness, males obtained higher scores in all the variables analyzed, except for the sit-and-reach test, corroborating the results of previous research [ 10 , 73 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, physical activity during adolescence plays a key role [ 15 ] in the maintenance of an active lifestyle during adulthood, as well as in the acquisition of other healthy lifestyle habits and the prevention of harmful lifestyle habits [ 16 ]. Furthermore, previous research has shown differences between males and females in the level of physical activity [ 7 ], with males practicing sports to a greater extent and with greater intensity than females [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We applied the "Barriers to Physical Activity" questionnaire [36] and the "International Physical Activity Questionnaire (IPAQ)" [37][38][39][40]. In addition, specific questions related to the COVID-19 pandemic were included in this questionnaire portion of our study.…”
Section: (A) Questionnairesmentioning
confidence: 99%